Tingkat Kadar Hemoglobin, Kebiasaan Sarapan dan Aktivitas Fisik Siswi Kelas VII SMP Swasta - Isnaini, Etik; Yuwono, Cahyo; Irawan, Fajar Awang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This article aims to find out the levels of hemoglobin in the body, breakfast or breakfast habits, and physical activity of female students. This article is a quantitative study with survey design and involves 108 students of the 7th grade of the Private School of Salatiga as a sample. Data analysis using descriptive of (minimum, maximum, average, standard deviation and percentage) obtained. The results of the study showed that female students had normal hemoglobin levels (97 per cent), with a regular breakfast habit (68 per cent) and heavy physical activity (93 per cent). The advice given is to keep an eye on health in the body to maintain fitness and minimize the occurrence of illness. Keywords: Anemia, Salatiga City, Women Student.